2016
DOI: 10.2131/jts.41.583
|View full text |Cite
|
Sign up to set email alerts
|

<i>In utero</i> exposure to diesel exhaust particles induces anxiogenic effects on male offspring via chronic activation of serotonergic neuron in dorsal raphe nucleus

Abstract: -Diesel exhaust consists of diesel exhaust particles (DEPs) and gaseous compounds. Because previous research suggested that in utero exposure to DEPs affected spatial learning and memory in male offspring, while epidemiological evidence suggested disturbances in affect after prenatal exposure to particulates, we hypothesized that DEP exposure during pregnancy might also disturb affect. Here, we explored the effects of in utero exposure to DEPs on anxiety in male ICR mice. DEP solutions were administered subcut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 65 publications
(83 reference statements)
0
6
0
Order By: Relevance
“…In mice, exposure to fine particles in utero and during the period corresponding to the third trimester of pregnancy in human beings was linked to structural changes in white matter. Other studies of in utero exposure in mice showed delayed cognitive development, increased anxiety and disrupted methylation of genes related to neurogenesis . In human beings, the available evidence on the effect of in utero exposure to air pollution on foetal and early brain structure and function is very scarce.…”
Section: Are Children More Vulnerable?mentioning
confidence: 99%
See 1 more Smart Citation
“…In mice, exposure to fine particles in utero and during the period corresponding to the third trimester of pregnancy in human beings was linked to structural changes in white matter. Other studies of in utero exposure in mice showed delayed cognitive development, increased anxiety and disrupted methylation of genes related to neurogenesis . In human beings, the available evidence on the effect of in utero exposure to air pollution on foetal and early brain structure and function is very scarce.…”
Section: Are Children More Vulnerable?mentioning
confidence: 99%
“…We propose to focus research on pre-natal life ( Table 1) because, as elaborated above, it can be considered as a critical window of exposure and provide a great opportunity for prevention and there have been reports on transgenerational brain effects in mice. 14,[25][26][27] Disruptions in the embryological process during pre-natal period could impair or make more fragile the brain for the rest of the life. 19 Moreover, pregnancy offers the opportunity of a more feasible and valid assessment of the cumulative exposure.…”
Section: Recommendations For the Future Research?mentioning
confidence: 99%
“…Within the existing literature, one study indicated that prenatal exposure to DEPs via subcutaneous injections of DEP suspensions leads to serotonergic neuronal activation of the dorsal raphe nucleus eventually resulting in an increased anxiety-like behavior in male offspring (Yokota et al, 2016). In a SVEE model in rats, whole-body exposures to gaseous constituents of exhaust, namely, CO 2 , CO, and NO 2 , resulted in elevated anxiety-like and depression-like behaviors and memory deficits in exposed rats (Salvi et al, 2017).…”
Section: Psychological Impact Of Vehicle Exhaust Emissionsmentioning
confidence: 99%
“…Interestingly, imbalances in the monoaminergic systems related to various neurocognitive disorders have also been noticed. Studies performed by Yokota et al in mice [4143] pointed out that maternal exposure to DE leads to perturbations of the offspring’s dopaminergic, noradrenergic and serotoninergic systems in specific brain regions that could be related to motor coordination and impulsive behavior disturbances. Nevertheless, some incongruence remains as another study has revealed contradictory monoaminergic changes [44], possibly based on different mixtures or routes used for exposure.…”
Section: Introductionmentioning
confidence: 99%
“…Animal research has confirmed and expanded the observed findings in humans, and has shown that the fetal stage is a critical period of vulnerability. Nevertheless, the effects on the CNS of a gestational exposure to air pollution at such a critical period for its anatomic and functional development remain questioned and have been poorly investigated in controlled conditions mimicking indirect human exposure and in early postnatal stages [3943]. Moreover, how the neuroanatomical continuum between brain and olfactory tissues is impacted by DE exposure remains largely unknown.…”
Section: Introductionmentioning
confidence: 99%